Overcoming Bottlenecks of Enzymatic Biofuel Cell Cathodes: Crude Fungal Culture Supernatant Can Help to Extend Lifetime and Reduce Cost. Issue 7 (5th July 2013) - Sané, Sabine; Jolivalt, Claude; Mittler, Gerhard; Nielsen, Peter J.; Rubenwolf, Stefanie; Zengerle, Roland; Kerzenmacher, Sven
Abstract Invited for this month′s cover is the Biofuel Cell research group of Sven Kerzenmacher at the University of Freiburg. The image illustrates that the wood‐degrading fungus Trametes versicolor can be used to resupply the redox enzyme laccase at an enzymatic biofuel cell cathode. Read the full text of the article on page 1209